Role of Human TRIM5α in Intrinsic Immunity - Nakayama, Emi E.; Shioda, Tatsuo (Frontiers in Microbiology, 2012)
Human immunodeficiency virus (HIV) has a very narrow host range. HIV type 1 (HIV-1) does not infect Old World monkeys, such as the rhesus monkey (Rh). Rh TRIM5α was identified as a factor that confers resistance, intrinsic immunity, to HIV-1 infection. Unfortunately, human TRIM5α is almost powerless to restrict HIV-1. However, human TRIM5α potently restricts N-tropic murine leukemia viruses (MLV) but not B-tropic MLV, indicating that human TRIM5α represents the restriction factor previously designated as Ref1. African green monkey TRIM5α represents another restriction factor previously designated as Lv1, which restricts both HIV-1 and simian immunodeficiency virus isolated from macaque (SIVmac) infection. TRIM5 is a member of the tripartite motif family containing RING, B-box2, and coiled-coil domains. The RING domain is frequently found in E3 ubiquitin ligase, and TRIM5α is thought to degrade viral core via ubiquitin proteasome-dependent and -independent pathways. The alpha isoform of TRIM5 has an additional C-terminal PRYSPRY domain, which is a determinant of species-specific retrovirus restriction by TRIM5α. On the other hand, the target regions of viral capsid protein (CA) are scattered on the surface of core. A single amino acid difference in the surface exposed loop between α-helices 6 and 7 (L6/7) of HIV type 2 (HIV-2) CA affects viral sensitivity to human TRIM5α and was also shown to be associated with viral load in West African HIV-2 patients, indicating that human TRIM5α is a critical modulator of HIV-2 replication in vivo. Interestingly, L6/7 of CA corresponds to the MLV determinant of sensitivity to mouse factor Fv1, which potently restricts N-tropic MLV. In addition, human genetic polymorphisms also affect antiviral activity of human TRIM5α. Recently, human TRIM5α was shown to activate signaling pathways that lead to activation of NF-κB and AP-1 by interacting with TAK1 complex. TRIM5α is thus involved in control of viral infection in multiple ways.